Characterization of magnetic and microwave absorption properties of multi-walled carbon nanotubes/Mn-Cu-Zr substituted strontium hexaferrite nanocomposites. (November 2016) - Rostami, Mohammad; Moradi, Mahmood; Alam, Reza Shams; Mardani, Reza
Graphical abstract: Highlights: ⿢ Nanoparticles of Mn-Cu-Zr substituted strontium hexaferrites are synthesized. ⿢ The nanocomposites of substituted strontium hexaferrites-MWCNT are fabricated. ⿢ The formation of the nanocomposites is confirmed with FESEM and TEM microscopy. ⿢ SrMn0.4 Cu0.4 Zr0.8 Fe10.4 O19 -MWCNT has the highest reflection loss. Abstract: The nanocomposites of multi-walled carbon nanotubes (MWCNT)/SrMnx Cux Zr2x Fe12-4x O19 ( x = 0.0, 0.2, 0.3, 0.4 and 0.5) were fabricated. The X-ray diffraction patterns (XRD) confirmed the formation of M-type hexaferrites crystal structure. Fourier transform infrared (FTIR) spectroscopy has been used to consider the chemical bonds in the nanocomposites. From field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM), the fabrication of the nanocomposites has been confirmed. The vibrating sample magnetometer (VSM) was used to investigate magnetic properties of the nanocomposites. Microwave absorption properties have been investigated by the vector network analyzer. It is found that the nanocomposites with x ⿥ 0.3 and 7% weight percentage of MWCNT possess the wide bandwidth of 6 GHz. The nanocomposite with the chemical composition of SrMn0.4 Cu0.4 Zr0.8 Fe10.4 O19 -MWCNT has the highest reflection loss, and as a result, it is the most appropriate material among these samples to be used as an electromagnetic wave absorber.